HOST–MICROBIOME AND PHAGE INTERACTIONS IN HEALTH AND DISEASE: MECHANISTIC INSIGHTS AND THERAPEUTIC IMPLICATIONS: Microbiology and biochemstery - Rasha Hameed Jasim; Mustafa Abd- almajeed Abd-alkareem; Yasameen Hameed Jasim (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
The human microbiome is a dynamic ecosystem, which has been found to combine microbial metabolism, immune regulation, and epithelial barrier functions to keep the host in a state of homeostasis. Disease related dysbiosis is increasingly being shown to be not merely a change in bacterial composition but a breakdown of the regulation of microbial ecosystems. At the heart of this regulation is the phageome that prevails in the gut virome and actively influences the dynamics of bacterial populations, functional capability and gene exchange. In this review, existing knowledge of mechanistic insights on host-microbiome and microbiome-phage interaction is synthesized, with focus on roles of microbial metabolites, immune sensing signals, and phage mediated ecology processes in shaping health and disease. We explain how disruptions of bacterial-phage interactions cause chronic inflammation, metabolic and immune pathology and therapy responses, and how the main methodological and conceptual problems restrict the current phageome studies. Incorporation of phage biology into microbiome models is vital to the future of ecosystem-based disease models, as well as to establish specific microbiome- and virome-directed treatments.